The facility management handbook - Cotts, David G. (AMACOM, 1999)
"The Facility Management Handbook, now updated for the realities of today's workplace, has everything you need - down to the last detail - to help you organize all your functional activities and create a productive, businesslike facility that integrates people, place, and purpose."--Jacket